Barley Ror1 encodes a class XI myosin required for mlo‐based broad‐spectrum resistance to the fungal powdery mildew pathogen. (31st August 2022) - Acevedo‐Garcia, Johanna; Walden, Kim; Leissing, Franz; Baumgarten, Kira; Drwiega, Katarzyna; Kwaaitaal, Mark; Reinstädler, Anja; Freh, Matthias; Dong, Xue; James, Geo Velikkakam; Baus, Lisa C.; Mascher, Martin; et al.
SUMMARY: Loss‐of‐function alleles of plant MLO genes confer broad‐spectrum resistance to powdery mildews in many eudicot and monocot species. Although barley ( Hordeum vulgare ) mlo mutants have been used in agriculture for more than 40 years, understanding of the molecular principles underlying this type of disease resistance remains fragmentary. Forward genetic screens in barley have revealed mutations in two Required for mlo resistance ( Ror ) genes that partially impair immunity conferred by mlo mutants. While Ror2 encodes a soluble N ‐ethylmaleimide‐sensitive factor‐attached protein receptor (SNARE), the identity of Ror1, located at the pericentromeric region of barley chromosome 1H, remained elusive. We report the identification of Ror1 based on combined barley genomic sequence information and transcriptomic data from ror1 mutant plants. Ror1 encodes the barley class XI myosin Myo11A (HORVU.MOREX.r3.1HG0046420). Single amino acid substitutions of this myosin, deduced from non‐functional ror1 mutant alleles, map to the nucleotide‐binding region and the interface between the relay‐helix and the converter domain of the motor protein. Ror1 myosin accumulates transiently in the course of powdery mildew infection. Functional fluorophore‐labeled Ror1 variants associate with mobile intracellular compartments that partially colocalize with peroxisomes. Single‐cell expression of the Ror1 tail region causes a dominant‐negative effect that phenocopies ror1 loss‐of‐function mutants. We define a myosin motor for the establishment of mlo ‐mediated resistance, suggesting that motor protein‐driven intracellular transport processes are critical for extracellular immunity, possibly through the targeted transfer of antifungal and/or cell wall cargoes to pathogen contact sites. Significance Statement: We report the identification of a barley ( Hordeum vulgare ) gene that is required for the agriculturally relevant broad‐spectrum powdery mildew resistance conditioned by mlo mutants. The gene encodes a class XI myosin motor protein that partly associates with peroxisomes and might be needed for the timely intracellular transport of defense‐related cargoes in the context of extracellular immunity.